Dari Limbah Jadi Berkah: Transformasi Minyak Jelantah Menjadi Sumber Penghasilan Tambahan Bagi Ibu Pkk Di Desa Tinggarjaya - Ulya Darojah; Abdullah Faqih Al Jauzie; Zuhrotul Aliffiyah; Indri Nur Azizah; Salsabila Nur Fadhilah; Adinda Fresky Mutiara Kafitasari; Zhafira Ardhia Pramesti Cahyani; Anggita Isty Intansari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The processing of used cooking oil into aromatherapy candles is a strategic effort to address household waste while creating new business opportunities. This innovation not only has economic value but also contributes to health and environmental benefits. Through a community service program conducted by KKN students, the PKK women’s group in Tinggarjaya Village was equipped with knowledge and skills to produce aromatherapy candles. The results showed that participants not only understood the material but also actively engaged in the practice. This program is expected to be sustainable and developed into small-scale household businesses, making used cooking oil utilization one of the community empowerment strategies aligned with sustainable development principles. The program applied the ABCD (Asset-Based Community Development) approach. In the Discover stage, key assets included active PKK women, abundant used cooking oil, and village support. In the Dream stage, participants envisioned turning waste into eco-friendly products with economic value. The Design stage involved training on health risks, hands-on candle-making, and entrepreneurship skills. In the Deliver stage, participants successfully produced candles, raised environmental awareness, and explored creative business opportunities. Finally, in the Destiny stage, sustainability was emphasized through potential innovations such as soap-making, supported by the village, aiming for an independent, healthy, and creative economy.